2015
DOI: 10.2169/internalmedicine.54.4335
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cholinesterase Is Inversely Associated with Body Weight Change in Men Undergoing Routine Health Screening

Abstract: Objective The purpose of this study is to investigate the relationships between serum cholinesterase and body weight change, in addition to incident obesity defined as a body mass index (BMI) of 25 kg/m 2 or greater. Methods A retrospective 5-year follow-up study was conducted. The crude incidence and hazard ratios (HRs) of obesity adjusted for the BMI and other confounders were calculated for cholinesterase quartiles in 1,412 men and 921 women. Partial correlation coefficients (PCCs) were calculated between c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The cholinesterase level can be increased under several conditions, including fatty liver, diabetes, and obesity ( 1 , 5 ). The profiles of the patients in the higher quartiles established by Mito et al suggested that the patients in higher quartiles might have metabolic disorders with higher body mass index ( 6 ), but some of the metabolic disorders such as diabetes and fatty liver, which might be reported by attending physicians, were not significantly different across quartiles ( 4 ). This implies that abnormally high cholinesterase levels may reflect the accumulation of visceral fat or an over-nutritional state beyond the acknowledged baseline characteristics ( 5 , 6 ), which can lead to atherosclerotic cardiovascular disease.…”
mentioning
confidence: 99%
“…The cholinesterase level can be increased under several conditions, including fatty liver, diabetes, and obesity ( 1 , 5 ). The profiles of the patients in the higher quartiles established by Mito et al suggested that the patients in higher quartiles might have metabolic disorders with higher body mass index ( 6 ), but some of the metabolic disorders such as diabetes and fatty liver, which might be reported by attending physicians, were not significantly different across quartiles ( 4 ). This implies that abnormally high cholinesterase levels may reflect the accumulation of visceral fat or an over-nutritional state beyond the acknowledged baseline characteristics ( 5 , 6 ), which can lead to atherosclerotic cardiovascular disease.…”
mentioning
confidence: 99%